Exploring neuropsychiatric symptoms in Friedreich ataxia - Karamazovová, Simona; Stovickova, Lucie; Jester, Dylan J; Matuskova, Veronika; Paulasova-Schwabova, Jaroslava; Kuzmiak, Michaela; Zumrova, Alena; Andel, Ross; Vyhnalek, Martin (Scientific reports, 2024)
Neuropsychiatric symptoms (NPS) are common in hereditary ataxias as a part of the cerebellar cognitive affective syndrome. In Friedreich ataxia (FRDA), one of the most common hereditary ataxias, depressive symptoms were previously reported, but little is known about other NPS. We aimed to study the presence and severity of a broad range of NPS in individuals with FRDA and assess the relationship between the NPS and the disease severity, cognition, and quality of life and to examine the concordance between the NPS reported by the patients and by their informants. Mild Behavioral Impairment Checklist (MBI-C), a questionnaire designed for screening NPS in the early stages of neurodegenerative diseases, was administered to informants of individuals with FRDA and healthy controls and to people with FRDA themselves. Compared to healthy controls, patients with FRDA scored significantly higher in the total MBI-C score, emotion dysregulation domain (corresponding to depression and anxiety), and decreased motivation domain. When assessed by caregiver, the total MBI-C score and several NPS domains correlated with activities of daily living. Only psychotic symptoms were related to ataxia severity and general cognition. When endorsed by patients, only the relation between few MBI-C domains and quality of life was observed. We found slight to moderate agreement between informant-rated and patient-rated scores. NPS, particularly emotion dysregulation and decreased motivation, are common and clinically relevant in FRDA and should receive more attention due to their potential impact on quality of life and the possibility of therapeutic intervention.
Keywords: Friedreichova ataxie; činnosti denního života; stupeň závažnosti nemoci; deprese; Cognition; Depression; Middle Aged; průzkumy a dotazníky; mužské pohlaví; studie případů a kontrol; Adult; mladý dospělý; Activities of Daily Living; kvalita života; kognice; Young Adult; ženské pohlaví; Humans; úzkost; Surveys and Questionnaires; Anxiety; lidé středního věku; Friedreich Ataxia; Case-Control Studies; dospělí; Female; Quality of Life; Severity of Illness Index; lidé; Male